Studying the priority of technical-tactical actions fulfillment among highly-qualified belt wrestlers during competitive activity - Suleimanov, G.; Boltikov, Y.; Solomahin, O.; Zemlenukhin, I.; Kaplev, A. (BIO Web of Conferences, 2020)
Dynamically developing kind of sport "Belt wrestling" undergoes serious changes nowadays in the structure of competitive combats and it makes specialists study combats and search for new ways of improving the forms and content of wrestlers` technical and tactical training. This article studies an urgent question of techniques fulfillment priority by highly-qualified belt wrestlers in the final combats of the biggest International competitions. From the held analysis of 48 combats among belt wrestlers during the final part of three World Cups and three World Championships among 18-20 year-old juniors we define 6 most frequently used techniques. They were used by the winners of the competitions. The article also presents detailed analysis of the held technical-tactical actions indices during the combat and the received for them points among highly-qualified wrestlers. It was stated that highly-qualified belt wrestlers have a wide arsenal of technical means for an effective fulfillment of technical-tactical actions during important combats. At the same time, we underline that in the held by them combats attacking and executing a counterattack actions prevail and wrestlers organize the combat in power oriented, aggressive and attacking manner.